Pengembangan E-Modul Berbasis Pendidikan STEM untuk Memfasilitasi Kemampuan Berpikir Kritis Siswa SMA - Arisanty, Defi; Risnanosanti, Risnanosanti; Hartati, Merri Sri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to produce and describe an e-module based on STEM (Science, Technology, Engineering, and Mathematics) education to facilitate the critical thinking skills of high school students. The research method used is a 4-D development model: define, design, development, and disseminate. The results show that the e-module's validation rate reached 93.33% for the material aspect and 87.62% for the design aspect, categorized as very valid. The practicality test for the e-module by mathematics teachers reached 95%, and the practicality test for students reached 85.43%, categorized as very practical. The effectiveness test for students reached 83.33%, and the critical thinking ability test showed an improvement in students' critical thinking skills after using the e-module in the learning process. In conclusion, the STEM Education-based e-module can facilitate high school students' critical thinking skills on sequences and series, presented in a PPT format that is easily accessible to students. Keywords: Sequences and Series, E-Modules, Critical Thinking Skills, STEM (Science, Technology, Engineering, and Mathematics)